Long‐term evaluation of vascular grafts with circumferentially aligned microfibers in a rat abdominal aorta replacement model. Issue 7 (7th February 2018) - Li, Wen; Chen, Jingrui; Xu, Pan; Zhu, Meifeng; Wu, Yifan; Wang, Zhihong; Zhao, Tiechan; Cheng, Quhan; Wang, Kai; Fan, Guanwei; Zhu, Yan; Kong, Deling
Abstract: Long‐term results of implants in small animal models can be used to optimize the design of grafts to further promote tissue regeneration. In previous study, we fabricated a poly(ɛ‐caprolactone) (PCL) bi‐layered vascular graft consisting of an internal layer with circumferentially aligned microfibers and an external layer with random nanofibers. The circumferentially oriented vascular smooth muscle cells (VSMCs) were successfully regenerated after the grafts were implanted in rat abdominal aorta for 3 months. Here we investigated the long‐term (18 months) performance of the bi‐layered grafts in the same model. All the grafts were patent. No thrombosis, aneurysm, or stenosis occurred. The endothelium maintained complete. However, most of circumferentially oriented VSMCs migrated to luminal surface of the grafts to form a neointima with uniform thickness. Accordingly, extracellular matrix including collagen, elastin, and glycosaminoglycan displayed high density in neointima layer while with low density in the grafts wall because of the incomplete degradation of PCL. A small amounts of calcification occurred in the grafts. The contraction and relaxation function of regenerated neoartery almost disappeared. These data indicated that based on the structure design, many other factors of grafts should be considered to achieve the regenerated neoartery similar to the native vessels after long‐term implantation. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2596–2604, 2018.